2021
DOI: 10.3390/plants10071381
|View full text |Cite
|
Sign up to set email alerts
|

Epiphytic Orchid Diversity along an Altitudinal Gradient in Central Nepal

Abstract: Epiphytic orchids are common in subtropical forests, but little is known about the factors that determine their diversity. We surveyed two sites (north-facing Phulchowki and south-facing Shivapuri hills), in the sub-tropical forest in the Kathmandu valley, central Nepal. Along five transects per site, spanning an altitudinal gradient of 1525–2606 m a.s.l., we recorded all epiphytic orchids and the host species on which they were growing. The data were analyzed using a generalized linear model (GLM) and redunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…In general, there are two main patterns of species richnessan altitude relationship: a monotonic decrease in number of species with altitude; and a hump-shaped pattern with the highest species number at mid-altitudes (Rahbek, 1995;McCain and Grytnes, 2010;Timsina et al, 2021). Nearly half of the studies showed that the hump-shaped patterns are the most common ones, whereas other studies suggested either a monotonic decrease or an increase in the number of species with altitude (McCain and Grytnes, 2010;Timsina et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, there are two main patterns of species richnessan altitude relationship: a monotonic decrease in number of species with altitude; and a hump-shaped pattern with the highest species number at mid-altitudes (Rahbek, 1995;McCain and Grytnes, 2010;Timsina et al, 2021). Nearly half of the studies showed that the hump-shaped patterns are the most common ones, whereas other studies suggested either a monotonic decrease or an increase in the number of species with altitude (McCain and Grytnes, 2010;Timsina et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In general, there are two main patterns of species richnessan altitude relationship: a monotonic decrease in number of species with altitude; and a hump-shaped pattern with the highest species number at mid-altitudes (Rahbek, 1995;McCain and Grytnes, 2010;Timsina et al, 2021). Nearly half of the studies showed that the hump-shaped patterns are the most common ones, whereas other studies suggested either a monotonic decrease or an increase in the number of species with altitude (McCain and Grytnes, 2010;Timsina et al, 2021). Although several hypotheses have been proposed to explain patterns of orchid diversity along the altitudinal gradient, most studies address the influence of climatic factors, then the mid-domain effect (MDE), while less attention has been paid to the species-area relationship (SAR).…”
Section: Introductionmentioning
confidence: 99%
“…Magnolia montana is also a medium to a tall tree that is common to lowland and lower montane forests throughout Sumatera, Peninsular Malaysia, Borneo, and Java (Tropical Plants Database 2021; MyBIS 2021). Aside from surface area, tall trees also provide various microhabitat conditions which can shelter various orchid species with different habitat preferences (Zhao et al 2015;Hernández-Pérez et al 2018;Zotarelli et al 2019;Timsina et al 2021). Both Ficus spp.…”
Section: Orchid Diversity and Microhabitat Characteristicsmentioning
confidence: 99%
“…The communities of epiphyte as good controls to evaluate species-specific interactions, also as indicators species of habitat disturbances and orchids have a good role as indicator species that adapt to abiotic IOP Publishing doi:10.1088/1755-1315/1016/1/012006 2 factors of the habitat [6], [7], [8]. Several research about epiphytic orchids and their host tree that have been carried out include: distribution on epiphytic orchid in Shimma wallichii tree [9], epiphyte host preference and host traits [3], spatial patterns of epiphytic orchid in Sempu island [10], research of host tree characteristics, distribution patterns, conditions of microclimate and diversity of epiphytic orchids [11], the role of orchids as indicator species of disturbed forest ecosystems in limestone mining areas in Georgia [8], diversity of epiphytic orchids at different elevations in the central Nepal region [12], analysis of the diversity of epiphytic orchids and their host-trees on Mount Lawu Magetan [13], diversity of epiphytic attached to the host trees [14], the species of host tree selected for the epiphytic orchid Epidendrum magnoliae Muhl (green fly orchid) in Georgia [15], types of host plants as indicators occurrence of Grammathophyllum scriptum in low land of Gunung Meja Natural Tourist Park [16] and there are many other research.…”
Section: Introductionmentioning
confidence: 99%